Description of Mathematical Critical Thinking Skills for Vocational High School Students during the COVID-19 Pandemic - Cantika Putriani; Indrie Noor Aini (EduMa: Mathematics education learning and teaching, 2022)
The Pandemic period made mathematics less understood by students, especially vocational students. Because of that, describing mathematical critical thinking skills need to be done so that teachers can improve the approach or learning method. This research aims to describe the essential skills of thinking of 10th-grade vocational high school students on the content of quadratic equations and functions. This type of research is descriptive quantitative research. The subjects in this study consisted of 25 students of SMK Negeri 1 Karawang grade 10 to determine the sample using the purposive sampling technique. The test instrument collected the research data in three validated description questions. This research indicates that students' critical thinking skills implemented through web-based learning media at SMK Negeri 1 Karawang are â€œmoderate categoryâ€. The final test results among 25 respondents consisted of three students within â€œhigh categoryâ€, seventeen students within â€œmedium categoryâ€, and five students within â€œlow categoryâ€. Moreover, the studentsâ€™ percentage level on critical thinking skills having 55% was deemed within â€œmoderate categoryâ€. The conclution is that the respondents' mathematical critical thinking skills are in the moderate category, so it is hoped that educators can improve the students' critical thinking skills by using learning methods, learning media, and teaching materials